Germacrone Attenuates Hepatic Stellate Cells Activation and Liver Fibrosis via Regulating Multiple Signaling Pathways - Li, Zhiyong; Wang, Zhilei; Dong, Fang; Shi, Wei; Dai, Wenzhang; Zhao, Jing; Li, Qiang; Fang, Zhi-e; Ren, Lutong; Liu, Tingting; Wei, Ziying; Mou, Wenqing; et al. (Frontiers in Pharmacology, 2021)
Liver fibrosis is an abnormal proliferation of connective tissue in the liver caused by various pathogenic factors. Chronic liver injury leads to release of inflammatory cytokines and reactive oxygen species (ROS) from damaged hepatocytes, which activates hepatic stellate cells (HSCs) to secrete extracellular matrix proteins, thereby leading to fibrosis. Thus, inhibition of hepatocyte injury and HSC activation, and promotion of apoptosis of activated HSCs are important strategies for prevention of liver fibrosis. In this study, we showed that the germacrone (GER), the main component in the volatile oil of zedoary turmeric, inhibited hepatic fibrosis by regulating multiple signaling pathways. First, GER improved the cell survival rate by inhibiting the production of ROS after hepatocyte injury caused by acetaminophen (APAP). In addition, GER inhibited the activation of HSCs and expression of collagen I by blocking TGF-β/Smad pathway in LX-2 cells. However, when the concentration of GER was higher than 60 μM, it specifically induced HSCs apoptosis by promoting the expression and activation of apoptosis-related proteins, but it had no effect on hepatocytes. Importantly, GER significantly attenuated the MCD diet-induced liver fibrosis by inhibiting liver injury and the activation of HSCs in vivo. In summary, GER can not only protect hepatocytes by reducing ROS release to avoid the liver injury-induced HSC activation, but also directly inhibit the activation and survival of HSCs by regulating TGF-β/Smad and apoptosis pathways. These results demonstrate that GER can be used as a potential therapeutic drug for the treatment of liver fibrosis.